UPAYA PENCAPAIAN TUJUAN PENDIDIKAN ISLAM DALAM PENDIDIKAN NASIONAL DIMASA PANDEMI COVID-19 - Fery Diantoro; Endang Purwati; Erna Lisdiawati (IAIN Ponorogo, 2021)
Starting in early 2020, Indonesia has been living life with the impact of the disaster, namely of the corona virus or also called as covid-19. Activities in various fields, especially education, face various problems in the process, which were initially carried out face-to-face/offline to online and of course this all affects the system and quality of education. Islamic education which has taken place as an inseparable part of the national education system has also experienced this impact. The writing of this article is to identify the difficulty of Islamic education in national education during the covid-19 pandemic, whose goal is to provide knowledge of the efforts made by Islamic education during the covid-19 pandemic. The results of the discussion show that Islamic education in national education during the covid-19 pandemic develops potential or provides creativity to students, teaches to always try in any activity, strives and prays to God Almighty, is responsible for all activities that should still be carried out. while online, maintain morals, manners, be independent, knowledgeable, and of course must keep the spirit. To optimize the function of Islamic religious education, it is necessary to maximize the program through efforts to equalize peers in schools, support facilities for activities, support from related parties, evaluateKeyword: Islamic Education, National Education, Covid-19.